1996
DOI: 10.1128/jvi.70.3.1365-1374.1996
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus with a deletion of genes spanning HindIII-J and -I displays altered cell and tissue tropism

Abstract: Murine cytomegalovirus (MCMV) gene products dispensable for growth in cell culture are likely to have important functions within the infected host, influencing tissue tropism, dissemination, or immunological responses against the virus. To identify such genes, our strategy was to delete large regions of the MCMV genome likely to contain genes nonessential for virus replication in NIH 3T3 cells. Mutant virus RV7 contained a deletion of 7.7 kb spanning portions of MCMV HindIII-J and -I. This virus grew comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The fcr-1 gene is nonessential for replication in cell culture and has no phenotype in vitro. Herpesvirus functions have been shown to modulate virus-host interactions such as antigen presentation and immune system control (2,4,12,15,17,31,34,37,(39)(40)(41), tissue tropism (3-5, 23, 27), virus spread (9,25,42), and the establishment of latency (33). Most of these functions are encoded by nonessential genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fcr-1 gene is nonessential for replication in cell culture and has no phenotype in vitro. Herpesvirus functions have been shown to modulate virus-host interactions such as antigen presentation and immune system control (2,4,12,15,17,31,34,37,(39)(40)(41), tissue tropism (3-5, 23, 27), virus spread (9,25,42), and the establishment of latency (33). Most of these functions are encoded by nonessential genes.…”
Section: Discussionmentioning
confidence: 99%
“…In view of our results, the reduced in vivo virulence of these recombinants can now be explained at least in part by the lack of the fcr-1 gene. It has been shown that the deletion mutant missing both the fcr-1 gene and the m137 gene grew normally in the IC-21 macrophage cell line (4). This indicates that the FcR acts differently from the neighboring genes M140 and/or M141, to which macrophages growth deficiency was mapped.…”
Section: Discussionmentioning
confidence: 99%
“…Resulting samples were serially diluted and plated in replicates on 96-well plates containing NIH/3T3 monolayers, which are permissive for MCMV replication. 28 Monolayers were monitored daily for up to 42 days. Based on visual detection of viral cytopathic effect, each well was scored as positive or negative.…”
Section: Quantitative Viral Culture For MCMVmentioning
confidence: 99%
“…Deletion of several MCMV non‐essential genes has proven to affect tissue tropism in vivo. For example, a recombinant virus (RV7) with a 7.7‐kb deletion spanning portions of the HCMV Hin dIII‐J and ‐I region has shown that genes m137, m138, M139, M140 and M141 are not essential for virus replication in vitro but are essential for virus replication in vivo [73–75]. The functions of these genes are largely unknown.…”
Section: Virus Replication and Tissue‐specificitymentioning
confidence: 99%